The three body problem in quasi-delicts determining liability when multiple persons are negligent - Valeña, Maria Patricia S. (2023)
In physics, a three-body problem is generally understood as the problem of determining the evolution of three masses under their own gravity. Adopting this phrase to the law on quasi-delicts, a three-body problem arises whenever the Supreme Court is faced with a situation where a liability must be apportioned among apposing parties, and the legal relationship between two or more negligent acts on one hand, and the resulting injury on the other, must be determined. This Article shall first discuss the existing frameworks used to deal with such situations; namely, the doctrine of intervening causes, the doctrine of last clear chance, and the rule on contributory negligence. It shall then illustrate the inconsistencies in their jurisprudential application throughout the years, leading to the confusion as to the appropriate applications of all three frameworks. As a remedy, this Article shall propose a framework to reconcile said inconsistencies by (a) adopting the doctrine of intervening causes as a general framework, (b) adopting into said framework the doctrine of last clear chance as a pseudo-efficient intervening cause that does not completely sever the chain of causation, and (c) using :antecedent negligence" to refer to the negligent act, abandoning the use of the term "contributory negligence" for that purpose.
Keywords: Last clear chance (Law); Contributory negligence